The use of nano-carbon as an alternative to multi-walled carbon nanotubes in modified electrodes for adsorptive stripping voltammetry - Lo, T; Aldous, L; Compton, R (2012)
We report the advantageous use of nano-carbon black as a much cheaper alternative to multiwalled carbon nanotubes as an electrode modifier for use in adsorptive stripping voltammetry. Namely, the adsorptive stripping voltammetry (AdsSV) of nicotine is compared and contrasted at an unmodified glassy carbon (GC) electrode and GC electrodes modified with either bamboo multiwalled carbon nanotubes (MWCNT) or carbon black. The approximately spherical, primary carbon black particles used possessed an average radius of 7 nm, and are a form of 'nano-carbon'. Their immobilisation on a GC resulted in a nanostructured surface with a large active surface area. Cyclic Voltammetry (CV), Square Wave Voltammetry (SWV) and Differential Pulse Voltammetry (DPV) were performed using the various systems. SWV resulted in a Limit of Detection (LOD) of 12.4 ± 0.2 μM at bare GC. CV gave the lowest LOD results for MWCNT and nano-carbon modified electrodes, with LOD values of 5.0 ± 0.3 and 2.0 ± 0.3 μM. Nano-carbon is highlighted to be a cheap, highly effective electrode modifier which facilitates the electroanalytical quantification of physiologically relevant concentrations of nicotine by AdsSV. © 2012 Elsevier B.V. All rights reserved.